THE ROLE OF WORKPLACE FLEXIBILITY IN ENHANCING EMPLOYEE RETENTION AMONG GENERATION Z: A LITERATURE REVIEW - Desi Rahmawati; Eko Santoso (Berajah Journal, 2026)
Generation Z is increasingly dominating the labor market and bringing changes to employee expectations regarding the work environment. One of the factors considered important in retaining Generation Z employees is workplace flexibility. This study aims to analyze the role of workplace flexibility in enhancing employee retention among Generation Z through a qualitative approach using library research. Data were obtained from various academic sources, including books, scientific journal articles, research reports, and other relevant publications discussing workplace flexibility, employee retention, and Generation Z in the workplace. The collected data were analyzed using descriptive qualitative analysis to identify patterns, themes, and relationships among the concepts studied. The findings indicate that workplace flexibility, such as flexible working hours, remote working, and hybrid working, plays a significant role in improving employee retention among Generation Z. Furthermore, factors such as work-life balance, job satisfaction, employee well-being, organizational commitment, and employee engagement help explain the relationship between workplace flexibility and employee retention. The study also reveals that the successful implementation of workplace flexibility is influenced by organizational culture, leadership support, and technological readiness. This research contributes to the human resource management literature and provides practical implications for organizations in designing retention strategies that align with the characteristics and expectations of Generation Z.